The Attitude and Knowledge of General Practitioners and Nurses Towards Severe Mental Illness in the Primary Care Facilities of the Seychelles Islands - Lisa Kissubi-Chang-Time; Athanasios Hassoulas; Anna-Lisa Labiche (BJPsych Open)
Aims: People with severe mental illness have a reduced life expectancy of 15–20 years compared with the general population. The current literature shows this vulnerable population are 2 to 3 times increased risk of dying from cardiovascular disease, 2 to 6 times more likely to die from respiratory disease, and an increased risk of chronic viral infections such as HIV and hepatitis C. Patient, medication, and healthcare system factors influence the morbidity and mortality of people with severe mental illness. Stigma and discrimination by healthcare workers is a key contributing factor. We conducted this novel study in the Seychelles Islands with the aim of assessing the attitude and mental health knowledge of general practitioners and nurses towards severe mental illness in all 16 government primary healthcare facilities. We also aimed to explore the association of attitude and knowledge variables with sociodemographic characteristics and compare the attitude and knowledge between the two groups. We hypothesized that the greater the knowledge and understanding of severe mental illness the more positive and supportive the attitude would be.